2000
DOI: 10.1111/j.1528-1157.2000.tb00323.x
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Double‐Blind, Randomized, Placebo‐Controlled Trial of Levetiracetam as Add‐On Therapy in Patients with Refractory Partial Seizures

Abstract: Summary:Purpose: To evaluate the efficacy and tolerability of levetiracetam (LEV, Keppra) as add-on therapy in patients with refractory partial seizures.Methods: In this European multicenter, double-blind, randomized, placebo-controlled trial, LEV (500 or 1,000 mg twice daily) was compared with placebo as add-on therapy in 324 patients with uncontrolled simple or complex partial seizures, or both, with or without secondary generalization. After enrollment, three parallel groups were assessed during a baseline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

25
375
4
19

Year Published

2001
2001
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 428 publications
(428 citation statements)
references
References 10 publications
25
375
4
19
Order By: Relevance
“…This finding supports the notion that LEV does not induce CYP 3A4, the isozyme responsible for contraceptive steroid hydroxylation. Although the study was performed with the recommended starting dose of LEV, other controlled clinical trials have indicated that LEV at doses Յ3,000 mg daily did not alter the plasma concentrations of any concomitantly administered AEDs (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…This finding supports the notion that LEV does not induce CYP 3A4, the isozyme responsible for contraceptive steroid hydroxylation. Although the study was performed with the recommended starting dose of LEV, other controlled clinical trials have indicated that LEV at doses Յ3,000 mg daily did not alter the plasma concentrations of any concomitantly administered AEDs (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in vitro assays using human liver fractions and specific marker activities have shown that LEV does not inhibit the most common drug-metabolizing enzymes, including CYPs (1A2, 2A6, 2C9, 2C19, 2D6, 2E1, 3A4), UGTs, and epoxide hydrolase (13). The low potential of LEV for drug interactions was noted in several clinical trials in which LEV was administered to patients with refractory seizures who were receiving other AEDs, including CBZ, LTG, PHT, VPA, PB, gabapentin (GBP), and primidone (PRM (14)(15)(16). Although these were not specifically druginteraction studies, LEV appeared to have no significant effect on the serum concentrations of other AEDs.…”
mentioning
confidence: 99%
“…Its exact mechanism of action is unknown. Common side effects include somnolence, fatigue, and dizziness (1)(2)(3)(4)(5)(6). Adverse behavioral effects include agitation, hostility, anxiety, apathy, emotional lability, and depersonalization.…”
mentioning
confidence: 99%